Artificial stepwise light harvesting system in water constructed by quadruple hydrogen bonding supramolecular polymeric nanoparticles - Xiao, Tangxin; Li, Xiuxiu; Zhang, Liangliang; Diao, Kai; Li, Zheng-Yi; Sun, Xiao-Qiang; Wang, Leyong (Chinese chemical letters, 2024)
Stepwise energy transfer is ubiquitous in natural photosynthesis, which greatly promotes the widespread use of solar energy. Herein, we constructed a supramolecular light harvesting system based on sequential energy transfer through the hierarchical self-assembly of M, which contains a cyanostilbene core flanked by two ureidopyrimidinone motifs, endowing itself with both aggregation-induced emission behavior and quadruple hydrogen bonding ability. The monomer M can self-assemble into hydrogen bonded polymers and then form supramolecular polymeric nanoparticles in water through a mini-emulsion process. The nanoparticles were further utilized to encapsulate the relay acceptor ESY and the final acceptor NDI to form a two-step FRET system. Tunable fluorescence including a white-light emission was successfully achieved. Our work not only shows a desirable way for the fabrication of efficient two-step light harvesting systems, but also shows great potential in tunable photoluminescent nanomaterials. An artificial light harvesting system based on supramolecular polymeric nanoparticles has been constructed. Sequential energy transfer had taken place in the system by the encapsulation of relay and final acceptors, resulting in tunable photoluminescence. [Display omitted]